The Effect of Emotional Intelligence and Competency on Employees Performance in BKPSDM Muaro Jambi - Lailatul Isnaini (International Journal of Education, Information Technology, and Others, 2020)
The purpose of this study was to determine the description of Emotional Intelligence and Competency on Employees Performance in BKPSDM Muaro Jambi Regency. This Research using explanatory research with a quantitative approach and data collection through a questionnaire. The sample used by 36 respondents. The result is that Emotional Intelligence has a positive and significant effect on employee’s performance. There is a significant effect of emotional intelligence on the employee’s performance as evidenced by the probability value (Sig) of the emotional intelligence variable is smaller than the significant level (0.043 <0.05). Thus it can be concluded that the higher the emotional intelligence possessed by employee’s performance, the higher the performance of BKPSDMD Muara Jambi Regency. Competency has a positive and significant effect on employee’s performance. The is a significant effect of competence on employee’s performance, as evidenced by the probability value (Sig) of the competency variable which is smaller than the significant level (0.024 <0.05). Thus it can be concluded that the higher the competence, the higher the employee’s performance of BKPSDMD Muara Jambi Regency